JOHANNINE DUALISM RECONSIDERED: BEYOND THE COSMOLOGICAL-EPISTEMOLOGICAL DIVIDE - Evans Winata; Ricko Andhika; Adi Prasetyo Wibowo (Jurnal Penelitian Progresif, 2026)
The persistent debate over the character of Johannine dualism has long been framed as a choice between two dominant positions: a cosmological reading that identifies two ontologically distinct realms (light/darkness, above/below), and an epistemological reading that reduces the dualism to contrasting human responses to divine revelation. This article argues that both positions, despite their genuine textual support, impose an anachronistic dichotomy onto the Johannine corpus. Drawing on close exegesis of John 1:1–18, 3:1–21, 8:23–47, 17:6–19, 1 John 4:7–8, and Revelation 12, and engaging the contributions of Jörg Frey, Jan van der Watt, and Catrin Williams alongside the classical scholarship of Bultmann, Dodd, Brown, and Lincoln, this article proposes a third framework: incarnational-relational dualism. This framework holds that the Johannine polarity is neither a metaphysical division between two realms nor a merely cognitive-ethical distinction, but rather a differentiation between two modes of existence constituted by one's participation in or rejection of the incarnate Logos. The proposed model is distinguished from the doctrine of perichoresis and from Chalcedonian categories, to which it is related but not reducible. Implications for Johannine hermeneutics and pastoral theology are considered.